KINERJA INTELLECTUAL CAPITAL PERBANKAN INDONESIA: PENERAPAN MODEL PULIC DAN ANALISIS PANEL DATA - Yenny Sugiarti (Jurnal Keuangan dan Perbankan, 2012)
This paper investigated the performance of intellectual capital of Indonesian banking industry for the period2007-2009. It sought to measure the Value Added Intellectual Coefficient (VAICTM) and to analyze the performanceof Indonesian banks. The Pulic model is utilized to estimate the intellectual capital coefficient, and thepanel data regression was applied to test the impacts of human capital and physical capital on intellectualcapital. The results of Pulic model showed that there were increasing number of top performance banks duringthe period of study, rising from 2 banks in 2007 to 4 banks in 2009. There was a slight decrease in the badperformance banks, from 9 banks in 2007 to 8 banks in 2009. Bank Mandiri bank appeared to be the onlygovernment bank that was classified as the top performer during the period of study, while Bank PAN Indonesia,Bank Victoria, and Bank Himpunan Saudara 1906 emerge to be the top performers among the privatebanks. The findings from panel data regression suggested that both human capital and physical capital hadpositive significant impacts on intellectual capital. When the estimation was done toward human capital andphysical capital separately, the results were closely similar to the results in the original model.